Pemberdayaan Santri Melalui Pendampingan Budidaya Anggrek Di Pondok Pesantren Nurul Quran, Desa Kebulusan, Kabupaten Kebumen - Ulinnuha, Zulfa; Farid, Noor; Dinuriah, Imastini (Universitas Syiah Kuala, 2024)
The Nurul Qur'an Islamic Boarding School, which is located 5 KM from the city center of Kebumen Regency, has great economic development potential because of its strategic location. In order to increase the independence of students, it is necessary to make efforts to provide students with skills. One of the efforts made is to provide orchid cultivation training to students. The location of Islamic boarding schools close to the city center provides opportunities for students to develop ornamental orchid cultivation. The high interest of city residents in ornamental plants is the main reason for choosing orchids as the focus of development. Orchids are considered to have high aesthetic value and stable sales value, making them the right choice to develop. This service aims to provide motivation, knowledge and skills to students regarding orchid cultivation, with the hope of creating student independence. The method applied involves providing materials related to repotting, plant maintenance including fertilizing, watering, and inducing orchid flowering. Discussion sessions, making demonstration plots, and assistance with orchid cultivation practices are also an integral part of the implementation method. The results of this service show an increase in the students' competence in orchid maintenance and they are able to form an orchid agribusiness forum which is managed independently by the students. Thus, this service not only provides benefits in terms of improving practical skills, but also opens up new economic opportunities for students at the Nurul Qur'an Islamic Boarding School.